PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BIOLOGI BERBASIS KONTEKSTUAL PADA MATERI SISTEM PENCERNAAN KELAS XI SMA - Devista, Liana; Risdawati, Renny; Nerita, Siska (Pendidikan Biologi, 2013)
ABSTRACTStudent Work Sheet (LKS) is a sheet contains work to be done by students. Sheet sare typically in the form of instructions, the steps to complete at ask and the task to be performed. LKS is a contextual-based instructional materials created as a guide in conducting Â learning, where work sheet sare presented leading todaily life so that the students are able to connect the material they learn to real world situations and encourage them to use it ineveryday life.This type of research is the development of research by using 4-D models that consists of 4 stages, define, design, develop and disseminate. At this stage of develop test the validity and practicalities. These data were analyzed with descriptive analysis. LKS validity test results from didactic aspects, technical construction and the validator shows that LKS produced valid with a value 88.8%. LKS practicalities of test results from the aspects of ease of use, the benefits, and time efficiency of learning by teachers and students indicate that the resulting practical worksheets to the value of 84.09%. This suggests that from this research has generated worksheets based contextual on the material digestive system is valid and practical.Â